ACTIVATION, OIL AND GAS POTENTIAL AND ANOMALIES OF PHYSICAL FIELDS IN SOME AREAS IN UKRAINE - Gordienko V.V.; Zavgorodnyaya O.V. (My University, 2001)
Data on anomalies of the heat flow, mantle gravity effect, helium isotope ratio and electrical conductivity of crustal rocks are analysed for some areas in Ukraine. It is shown that such data correlate with the recent activation process which is also responsible for some hydrocarbon deposits.